Carbon and Water Footprints Within an Environmental Laboratory: Water, Energy, and Packaging Management Strategies - Villamar-Ayala, C (Elsevier B.V., 2025)
Environmental laboratories can be spaces where water, energy, and resources can be used more efficiently. The objective of this study is to evaluate the carbon and water footprints present in an environmental laboratory based on water, energy, and resource (packaging) management. To achieve this, life cycle analysis is applied (ISO 14040:2006, ISO 14044:2007) to 17 assay water (natural water/wastewater) types from an accredited environmental laboratory (ISO/IEC 17025). System boundaries correspond to cradle to gate, and 1 analyzed water sample is used as a functional unit. This study evaluates several factors baseline scenario, energy consumption reduction, 100 % renewable energy matrix, and material consumption reduction. Results show that under normal conditions the laboratory generated a carbon footprint of 10.10 kg CO2-eq/sample (82 % energy used), and a water footprint of 11.76 m3/sample (97 % indirect water). A 100 % renewable energy matrix improved laboratory environmental performance (75 % reduction carbon footprint), decreasing emissions up to 12 times (1,583 kg CO2-eq/year). Meanwhile, material consumption reduction considering the laboratory accreditation (i.e. smaller glass containers) improved the laboratory environmental performance (up to 6 % reduced water footprint), reducing direct water consumption up to 0.3 %. Although costs are not significantly affected by these scenarios, savings in energy consumption based on phantom power in equipment (which can be disconnected) can reduce the cost per water sample analyzed by 7.8 % (83 USD/year). The water and carbon footprint measuring in accredited environmental laboratories opens opportunities for the incorporation of different strategies that incorporate sustainability, and not only analytical quality (ISO 17025). © 2025 The Author(s)